(untitled) (Research, Society and Development, 2022)
Agriculture has evolved every day in Brazil, making the country one of the largest producers and exporters of grains, thereby raising the Brazilian GDP, especially after the COVID-19 pandemic, where Brazil had a growing rise in the economic balance. Taking into account the data in tons and percentages of growth referring to exported cereals, Brazil became a power in the year 2021. To better understand the functioning of agribusiness in Brazil, this bibliographical research was elaborated from data and reports published on academic article platforms and in materials presented by IBGE, CNA, IPEA and government institutes. It appears that in this agribusiness scenario, soy is more prominent in terms of production compared to other grains produced and exported by Brazil. Finally, the article developed here tends to address from future projections of the Gross Value of production to the important influence of agribusiness on the Brazilian GDP, evidencing its high relevance for the Brazilian economy. Based on recent studies, it is already clear that the country will be one of the world’s main hubs for the production of biofuels and cotton.